2021
DOI: 10.2196/30674
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Apps With a Medication List Functionality for Older Adults With Heart Failure Using the Mobile App Rating Scale and the IMS Institute for Healthcare Informatics Functionality Score: Evaluation Study

Abstract: Background Managing the care of older adults with heart failure (HF) largely centers on medication management. Because of frequent medication or dosing changes, an app that supports these older adults in keeping an up-to-date list of medications could be advantageous. During the COVID-19 pandemic, HF outpatient consultations are taking place virtually or by telephone. An app with the capability to share a patient’s medication list with health care professionals before consultation could support cli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…This tool is based on seven functionality criteria and four functional subcategories detailed in the report of the IQVIA Institute for Healthcare Informatics [ 21 , 45 ]. In some previous studies [ 26 , 43 , 45 ], this tool was used along with the MARS tool to rate mobile health app features. The IQVIA functionality score focuses on the availability of the 11 previously determined functionalities, and finally, each mobile app gives a score between 0 and 11.…”
Section: Introductionmentioning
confidence: 99%
“…This tool is based on seven functionality criteria and four functional subcategories detailed in the report of the IQVIA Institute for Healthcare Informatics [ 21 , 45 ]. In some previous studies [ 26 , 43 , 45 ], this tool was used along with the MARS tool to rate mobile health app features. The IQVIA functionality score focuses on the availability of the 11 previously determined functionalities, and finally, each mobile app gives a score between 0 and 11.…”
Section: Introductionmentioning
confidence: 99%
“…A review on apps with a medication list functionality reported that some apps had a poor interface and did not provide sufficient instructions on how to record medication-taking histories and set medication reminders. 27 Polypharmacy may exacerbate such issues, which could possibly explain why it was found to be associated with a lower likelihood of app use and use intention in our study. Second, most medication reminder apps use English as the default or only language.…”
Section: Discussionmentioning
confidence: 69%
“…We suggest three possible reasons for the low prevalence of medication reminder app use and use intention. First, studies have found that such apps have complex interfaces, and user-unfriendly and dense usage instructions, 27 , 28 which may make app sign-up and navigation difficult for older adults with lower educational attainment. A review on apps with a medication list functionality reported that some apps had a poor interface and did not provide sufficient instructions on how to record medication-taking histories and set medication reminders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors distinguished among apps for patients, apps for health professionals, and apps that can be used by both groups. Recent studies on patient-focused drug apps have analyzed those that help patients understand and take their medications or those with a medication list function [ 28 , 29 ]. In addition, apps for treatment adherence have been the subject of intensive research [ 30 - 35 ].…”
Section: Discussionmentioning
confidence: 99%